Acute Ankle Sprain Management: An Umbrella Review of Systematic Reviews - Gaddi, Diego; Mosca, Angelo; Piatti, Massimiliano; Munegato, Daniele; Catalano, Marcello; Di Lorenzo, Giorgia; Turati, Marco; Zanchi, Nicolò; Piscitelli, Daniele; Chui, Kevin; Zatti, Giovanni; Bigoni, Marco (Frontiers in Medicine, 2022)
Even though ankle sprains are among the most frequent musculoskeletal injuries seen in emergency departments, management of these injuries continues to lack standardization. Our objective was to carry out an umbrella review of systematic reviews to collect the most effective evidence-based treatments and to point out the state-of-the-art management for this injury. PubMed, Scopus, Web of Science, and the Cochrane library were searched from January 2000 to September 2020. After removing duplicates and applying the eligibility criteria, based on titles and abstracts, 32 studies were screened. At the end of the process, 24 articles were included in this umbrella review with a mean score of 7.7/11 on the AMSTAR quality assessment tool. We found evidence supporting the effectiveness of non-surgical treatment in managing acute ankle sprain; moreover, functional treatment seems to be preferable to immobilization. We also found evidence supporting the use of paracetamol or opioids as effective alternatives to non-steroidal anti-inflammatory drugs to reduce pain. Furthermore, we found evidence supporting the effectiveness of manipulative and supervised exercise therapy to prevent re-injury and restore ankle dorsiflexion.